Phonation and Stuttering - HP, Anitha (Journal of All India Institute of Speech and Hearing)
The present study was conducted to investigate the effect of whispering and changes in intensity of voice on the frequency of stuttering and the rate of speech. Nine stutterers read under four experimental conditions. Condition A (reading in whispering), condition B (reading at 60dB SPL), condition C (reading at 70dB SPL) and condition D (reading at 80dB SPL). Results showed that stuttering was significantly reduced with increase in intensity and stutterers became more fluent when they whispered. Rate of speech was significantly reduced in all conditions in which stuttering was significantly reduced. The results are discussed and explained on the basis of enhanced laryngeal feedback. Stuttering has been explained in many ways and the literature on theories of stuttering run into volumes. But no one theory explains satisfactorily all the aspects of stuttering. The recent investigations concerning the cause and nature of stuttering emphasize on the role of phonatory behaviour in stuttering. Larynn has been held responsible for stuttering to occur. A number of studies have directly or indirectly indicated phonatory involve- ment in stuttering (Adams and Hayden 1976, Adams and Reis 1971,1974, Adams et al,1976, Agneilo and Wingate 1971, Agnello, Wingate and Wendell 1974, Brennel, Perkins and Soderberg 1972, Charie Muller 1963, Conture et al,1974, Freeman and Ushijima 1978, Fujita 1966, Manning and Coujal 1976, Schwartz 1974, Stackweather et al, 1976, Wingate 1969b, Wyke 1974). Wingate (1969), after an analysis of various conditions under which stutterers enjoy ’artificial fluency’ inferred that ’vocalization’ is a crucial element in stuttering. Wingate (1970) further argued that reduction in stuttering associated with changes in audition is due to changes induced in vocalization. Adams and Moore (1972), and Adams and Hutchinson (1974), observed that as the intensity of mask- ing noise was increased, stutterers became more fluent, increased their vocal intensity and spoke at slower speech rates. Several authors have reported that stuttering is markedly reduced during whispering (Johnsen and Rosen 1937, Bloodstein 1950, Van Riper 1971, Perkins, Rudas and Bell 1976, Commodore and Cooper, 1978). investigated the effect of varying intensity on stuttering. Twenty-eight stutterers read a passage containing all voiced phonemes and a passage containing both voice and voiceless phonemes under three conditions, soft voice, normal voice and aloud voice when 75dBSPL of white noise was presented through earphones. More stuttering was observed in normal voice condition with all voiced phoneme prose. Stuttering was reduced while using soft voice and while using loud voice. The literature suggests that phonation is an important factor in stuttering and changes in certain aspects of phonation bring about significant changes in the frequency of stuttering. Therefore, in this study it was proposed to investigate the influence of whispering and the influence of varying intensity of voice on stuttering. Ramig (1980), studied the effect of varying pitch on the frequency of stuttering. He found a significant reduction in stuttering with reduction in reading rate as the stutterers varied their picth above and below their habitual pitch. Reis (1974),